Using Lignosellulose Waste as a Xylanase Production Media of Mold Isolated from Rice Straw of Coastal-field - Utarti, Esti; Siswanto, S. (Jurnal ILMU DASAR, 2018)
Hemicellulose is one of lignocellulose waste component, so that xylanase is one of importance enzyme of lignocellulose waste biodegradation. Molds as main decomposer lignosellulose waste has enzyme activities higher than yeast and bacteria. The aim of the research is to find mold that have xylanolitic activity using lignocellulose waste as media production. The research consist of isolations and screening mols from coastal-field of watu Ulo Jember, xylanase production using lignocellulose waste and idntification of mold which has the highes xylanase activity. A total of 66 molds isolated from rice straw in coastal-field of Watu Ulo Jember. There were screened for their xylanase activity. In semiquantitatively screen on Oat Spelt Xylan plate, the result showed that 62 have xilanolytic activities. Based on clearing zone production, isolates ESW A1 (3.2), ESW A5 (3.1), ESW C 16 (3.26), ESW D4 (3.0) and ESW D15 (3.21) have xilanase activity index higher than others. Furthermore, quantitative analysis using wheat bran, rice straw and baggase in basic salt Mandel’s modification media showed that xylanase activity of isolate ESW D4 was higher on rice straw 3% as substrate production with activity 2.66 U/mL. Isolate ESW D4 identified as Aspergillus foetidus so that called as Aspergillus foetidus ESW D4. Keywords: rice straw, coastal-field, Aspergillus foetidus ESW-D